Phytophthora Root Rot Resistance in Soybean E00003. Issue 2 (1st March 2014) - Zhang, Zhongnan; Hao, Jianjun; Yuan, Jiazheng; Song, Qijian; Hyten, David L.; Cregan, Perry B.; Zhang, Guorong; Gu, Cuihua; Li, Ming; Wang, Dechun
ABSTRACT: Phytophthora root rot (PRR) is a devastating disease in soybean [ Glycine max (L.) Merr.] production. Michigan elite soybean E00003 is resistant to Phytophthora sojae and has been used as a resistance source in breeding. Genetic control of PRR resistance in this source is unknown. To facilitate marker‐assisted selection (MAS), the PRR resistance loci in E00003 and their map locations need to be determined. In this study, a genetic mapping approach was used to identify major PRR‐resistant loci in E00003. The mapping population consists of 240 F4 –derived lines developed by crossing E00003 with the P. sojae susceptible line PI 567543C. In 2009 and 2010, the mapping population was evaluated in the greenhouse for PRR resistance against P. sojae races 1, 4, and 7, using modified rice ( Oryza sativa L.) grain inoculation method. The population was genotyped with seven simple sequence repeat (SSR) and three single nucleotide polymorphism (SNP) markers derived from bulk segregant analysis. The heritability of resistance in the population ranged from 83 to 94%. A major locus, contributing 50 to 76% of the phenotypic variation, was mapped within a 3 cM interval in the Rps 1 region. The interval was further saturated with more BARCSOY SSRs and SNPs with TaqMan assays. Two SSRs and three SNPs within the Rps 1k gene were highly associated with PRR resistance in the mapping population. The major resistance gene in E00003 is either allelic or tightly linked to Rps 1k. The molecular markers located in the Rps 1k gene can be used to improve MAS for PRR resistance.